Method in theology - Lonergan, Bernard J. F.; Doran, Robert M., 1939-; Dadosky, John D., 1966- (Toronto ; Buffalo ; London : Published for Lonergan Research Institute of Regis College, Toronto, by University of Toronto Press, 2017)
In Method in Theology, Vol. 14, Lonergan's intention was to provide a set of methods that would guide a collaborative community in the ongoing construction of a theology that would move from recovery of the data through resolution of conflicts to contemporary formulations and applications.
6 Ongoing Contexts7 The Ongoing Discovery of Mind: Part 2; 8 The Development of Doctrines; 9 The Permanence of Dogmas; 10 The Historicity of Dogmas; 11 Pluralism and the Unity of Faith; 12 The Autonomy of Theology; 13 Systematics; 1 The Function of Systematics; 2 Closed Options; 3 Mystery and Problem; 4 Understanding and Truth; 5 Continuity, Development, Revision; 14 Communications; 1 Meaning and Ontology; 2 Common Meaning and Ontology; 3 Society, State, Church; 4 The Christian Church and Its Contemporary Situation; 5 The Church and the Churches; Appendix 1: The New Context
The first edition was published in 1972.
Includes bibliographical references (pages 401-409) and index.
Description based on print version record.
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Theology -- Methodology; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books